Biomass Feedstock Availability for the Supply of Bioenergy in the Lerma Valley (Salta, Argentina): an Evaluation for Territorial Energy Planning - Manrique, Silvina Magdalena (2014)
Argentina plans to reach from 3% to 10% biomass participation for the internal supply of primary energy for 2015. However, biomass exploitation requires detailed studies at a local level for territorial energy planning, to achieve the expected energy and environmental benefits. This study, performed in the north of Argentina (Lerma Valley, province of Salta) is a step in this direction. The objective was to identify, characterize and quantify biomass feedstock availability in the region and its energy supply, studying the demand and utilization alternatives; and building different methodologies of quantification. The feedstock examined includes agricultural waste (AWB), municipal solid waste (MSW), and woody biomass (three main ecosystems and four species of Acacias spp.). They are annually producing 17,800 t.yr -1 (equivalent to 206,000 GJ.yr-1) of AWB; 24,100 t.yr-1 (around 34,000 GJ.yr-1 as biogas) of MSW (wet weight) and 213,000 t.yr-1 (or 3.1 million of GJ.yr -1) of woody biomass. The Acacias constitute 74% of the Shrubland’s potential bioenergy (213,000 GJ.yr-1). This report will make possible the application of realistic energy projects for the area, promoting efficient exploitation of resources and generating positive local impact. The main bottlenecks for the implementation of such projects and some possible strategic solutions are identified. The proposed methodologies might be used to other geographical regions, within programs of territorial energy planning. In addition, the new data set of available worldwide biomass resources and the scientific knowledge in the field of bioenergy that has been generated, both constitute fundamental contributions for bioenergy promotion.